To Join or Not to Join: Decision Points Along the Pathway to Double-Strand Break Repair vs. Chromosome End Protection - Ackerson, Stephanie M.; Romney, Carlan; Schuck, P. Logan; Stewart, Jason A. (Frontiers in Cell and Developmental Biology, 2021)
The regulation of DNA double-strand breaks (DSBs) and telomeres are diametrically opposed in the cell. DSBs are considered one of the most deleterious forms of DNA damage and must be quickly recognized and repaired. Telomeres, on the other hand, are specialized, stable DNA ends that must be protected from recognition as DSBs to inhibit unwanted chromosome fusions. Decisions to join DNA ends, or not, are therefore critical to genome stability. Yet, the processing of telomeres and DSBs share many commonalities. Accordingly, key decision points are used to shift DNA ends towards DSB repair versus end protection. Additionally, DSBs can be repaired by two major pathways, namely homologous recombination (HR) and non-homologous end joining (NHEJ). The choice of which repair pathway is employed is also dictated by a series of decision points that shift the break towards HR or NHEJ. In this review, we will focus on these decision points and the mechanisms that dictate end protection versus DSB repair and DSB repair choice.